Autopresentación perfeccionista e imagen corporal mediada por la autocompasión - Ferreira Rocha Nunes, Isabela; Evangelho Hernandez, José Augusto (Pontificia Universidad Católica del Perú, 2025)
This study investigated the relationship between perfectionist self-presentation and body image and the mediating effect of self-compassion. Participated 708 university students from public and private Higher Education Institutions aged between 18 and 40 years old. The following instruments were completed: Perfectionistic Self-Presentation Scale, Self-Compassion Scale - Short Form and Escala de Avaliação da Satisfação com a Imagem Corporal. The results did not identify differences between the groups. The correlations between the variables were significant. The mediating effect of self-compassion between perfectionist self-presentation and satisfaction with body image was confirmed. The findings indicated that promoting self-compassion can reduce the effects of perfectionist self-presentation on satisfaction with body image.

Este estudio investigó la relación entre la autopresentación perfeccionista y la imagen corporal y el efecto mediador de la autocompasión. Participaron 708 universitarios de Instituciones de Educación Superior públicas y privadas con edades comprendidas entre 18 y 40 años. Se completaron los siguientes instrumentos: Perfectionistic Self-Presentation Scale, Self-Compassion Scale - Short Form y Escala de Avaliação da Satisfação com a Imagem Corporal. Los resultados no identificaron diferencias entre los grupos. Las correlaciones entre las variables fueron significativas. Se confirmó el efecto mediador de la auto-compasión entre la autopresentación perfeccionista y la satisfacción con la imagen corporal. Los hallazgos indicaron que promover la autocompasión puede reducir los efectos de la autopresentación perfeccionista sobre la satisfacción con la imagen corporal.

Este estudo investigou a relação entre autoapresentação perfeccionista e imagem corporal e o efeito mediador da autocompaixão. Participaram 708 universitários de Instituição de Ensino Superior pública e privada com idades entre 18 e 40 anos. Foram preenchidos os instrumentos: Perfectionistic Self-Presentation Scale, Self-Compassion Scale - Short Form e Escala de Avaliação da Satisfação com a Imagem Corporal. Os resultados não identificaram diferenças entre os grupos. As correlações entre as variáveis foram significativas. O efeito mediador da autocompaixão entre autoapresentação perfeccionista e satisfação com a imagem corporal foi confirmado. Os achados indicaram que a promoção da autocompaixão pode reduzir os efeitos da autoapresentação perfeccionista na satisfação com a imagem corporal.
Perfectionistic self-presentation and body image mediated by self-compassion
Autoapresentação perfeccionista e imagem corporal mediadas pela autocompaixão
Keywords: Perfectionist self-presentation; Self-compassion; Body image; Autopresentación perfeccionista; Autocompasión; Imagen corporal; Autoapresentação perfeccionista; Autocompaixão; Imagem corporal; https://purl.org/pe-repo/ocde/ford#5.01.00